Epigenetic Regulation of Autophagy Beyond the Cytoplasm: A Review - Shi, Yin; Shen, Han-Ming; Gopalakrishnan, Vidya; Gordon, Nancy (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a highly conserved catabolic process induced under various stress conditions to protect the cell from harm and allow survival in the face of nutrient- or energy-deficient states. Regulation of autophagy is complex, as cells need to adapt to a continuously changing microenvironment. It is well recognized that the AMPK and mTOR signaling pathways are the main regulators of autophagy. However, various other signaling pathways have also been described to regulate the autophagic process. A better understanding of these complex autophagy regulatory mechanisms will allow the discovery of new potential therapeutic targets. Here, we present a brief overview of autophagy and its regulatory pathways with emphasis on the epigenetic control mechanisms.